2015
DOI: 10.1097/wnf.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Terazosin for the Treatment of Trauma-Related Nightmares

Abstract: The selective α1-adrenergic antagonist prazosin has been shown in multiple studies to be effective in targeting trauma-related nightmares in posttraumatic stress disorder. There are limited data regarding the effectiveness of another selective α1-adrenergic antagonist terazosin for the treatment of trauma-related nightmares. We present 4 cases in which terazosin was effectively used to treat nightmares as a second-line agent after prazosin failure. Further studies are needed to validate terazosin as an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Terazosin is another α-1 adrenergic antagonist that has been reported to reduce nightmares associated with PTSD. 69 , 70 While terazosin did not achieve full recall cessation, reduction of symptoms was described on 64% of the trials with dose ranging between 2.0 and 5.0 mg. 71 Similarly, doxazosin (1.0–6.0 mg) has shown promise in PTSD nightmares. 72 , 73 Because of improved absorption profile and longer half-life and its availability as an extended release, doxazosin may offer significant advantages over prazosin in clinical practice.…”
Section: Approach To Managementmentioning
confidence: 98%
“…Terazosin is another α-1 adrenergic antagonist that has been reported to reduce nightmares associated with PTSD. 69 , 70 While terazosin did not achieve full recall cessation, reduction of symptoms was described on 64% of the trials with dose ranging between 2.0 and 5.0 mg. 71 Similarly, doxazosin (1.0–6.0 mg) has shown promise in PTSD nightmares. 72 , 73 Because of improved absorption profile and longer half-life and its availability as an extended release, doxazosin may offer significant advantages over prazosin in clinical practice.…”
Section: Approach To Managementmentioning
confidence: 98%
“…Nirmalani-Gandhy and colleagues have described the cases of four combat veterans (three men and one woman) with chronic PTSD who failed a prazosin trial, but who showed improvements in nightmares with terazosin, another alpha-1 noradrenergic antagonist [43]. Effective terazosin doses ranged between 2 mg titrated up to 10 mg.…”
Section: Alpha-1 Noradrenergic Antagonistsmentioning
confidence: 99%